Death burden of high systolic blood pressure in Sichuan Southwest China 1990-2030 - Zhuo Wang; Yu Luo; Shujuan Yang; Mingliang Zuo; Rong Pei; Jun He; Yin Deng; Maigeng Zhou; Li Zhao; Hui Guo; Kun Zou (BMC, 2020)
Abstract Background Hypertension is highly prevalent and is the primary risk factor for cardiovascular disease (CVD) and chronic kidney disease (CKD). While declining in some developed countries, it is increasing rapidly in some developing countries. Sichuan province is the largest and underdeveloped region in southwest China, with 486 thousand square kilometers, more than 80 million residents, unbalanced economic development, and high prevalence, low awareness, low treatment and low control rate of hypertension. We forecasted the death burden due to high systolic blood pressure (SBP) in Sichuan from 1990 to 2030, to raise the awareness of public and government of the importance and benefits of hypertension control. Methods We conducted secondary analysis based on data of Global Burden of Disease (GBD) 1990-2015, and predicted the population SBP level, population attributable fraction, and death burden for people aged 30-69 under different scenarios in 2030. Results Comparing with natural trend, if the prevalence of high SBP can be reduced relatively by 25% by 2030, the deaths of non-communicable chronic diseases (NCDs), CVD and CKD would be reduced by 27.1 thousand, 26.2 thousand and 0.8 thousand for people aged 30-69; the mortality would be reduced by 10.8, 32.8 and 16.0%; and the premature mortality would be reduced by 9.9, 32.0 and 16.0%, respectively. Conclusions Controlling or decreasing the prevalence of high SBP can significantly reduce the deaths, death rate and premature mortality of NCDs, CVD and CKD for the 30-69 years old population in Sichuan. There would be huge benefits for the governments to take cost-effective measures to control or reduce the prevalence of hypertension.